2018
DOI: 10.5742/mewfm.2018.93211
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Schema Therapy on Body-Image, Self-Concept, Maladaptive Schemas in Patients with Body Dysmorphic Disorder

Abstract: This study aimed to evaluate the effectiveness of schema therapy on body-image, self-concept, and maladaptive schemas in patients with body dysmorphic disorder. This is a quasi-experimental study, with pretest-posttest research plan and follow-up services. The research population comprised all patients with body dysmorphic disorder in Ahwaz city. The sample consisted of 10 people from this population having dysmorphic disorder whose selection was done randomly and when chosen, they were divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Given that the specialized treatment package for women with BDD was designed and implemented for the first time in this research, there are no direct previous studies to compare these particular findings. However, these results can be indirectly aligned with studies confirming the positive effectiveness of schema therapy on the psychological status of individuals with BDD (Aghili & Hejazi, 2022;Farhadi et al, 2021;Kindynis et al, 2013;Mahmoudiyandastnaee et al, 2019;Montazeri et al, 2013;Morvaridi et al, 2019;Peeters et al, 2022;Pondehnezhadan & Fard, 2018;Simpson et al, 2010).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…Given that the specialized treatment package for women with BDD was designed and implemented for the first time in this research, there are no direct previous studies to compare these particular findings. However, these results can be indirectly aligned with studies confirming the positive effectiveness of schema therapy on the psychological status of individuals with BDD (Aghili & Hejazi, 2022;Farhadi et al, 2021;Kindynis et al, 2013;Mahmoudiyandastnaee et al, 2019;Montazeri et al, 2013;Morvaridi et al, 2019;Peeters et al, 2022;Pondehnezhadan & Fard, 2018;Simpson et al, 2010).…”
Section: Discussionsupporting
confidence: 67%
“…Since the specialized treatment package for women with BDD was designed and used for the first time in this research, there is no research available to directly compare the results of this part of the study with previous studies. However, this part of the results can be indirectly aligned with studies that have confirmed the positive effectiveness of schema therapy on the psychological status of individuals with BDD (Aghili & Hejazi, 2022;Farhadi et al, 2021;Kindynis et al, 2013;Mahmoudiyandastnaee et al, 2019;Montazeri et al, 2013;Morvaridi et al, 2019;Peeters et al, 2022;Pondehnezhadan & Fard, 2018;Simpson et al, 2010). This part of the findings also indirectly correlates with a series of studies that have confirmed the positive effectiveness of schema therapy on maladaptive schemas; Babazadeh (2019) reported that schema therapy affects maladaptive primary variables in the areas of rejection and abandonment, self-perception, limitation, and hypervigilance.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations